New kata evaluation in top-level karate: analysis of frequency and score of katas in K1 Premiere League - Novosad, A.; Argajova, J.; Augustovicova, D. (Archives of Budo, 2020)
Background and Study Aim: With the new kata evaluation procedure, seven judges evaluate the kata. Scores are given according to the technical and athletic presentation of the katas. This improvement could cause changes in competition trends. The goal of the study was the knowledge about frequency and score of performed katas at the 2019 Karate 1 premiere league.